2016
DOI: 10.1061/(asce)em.1943-7889.0001174
|View full text |Cite
|
Sign up to set email alerts
|

Memory Surface Hardening Model for Granular Soils under Repeated Loading Conditions

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms 1 The prediction of the stress-strain response of granular soils under large numbers of repeated 19 loading cycles requires subtle changes to existing models, although the basic framework of 20 kinematic hardening/bounding surface elasto-plasticity can be retained. Extending an existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…While the achievement of precise and accurate measurement of specimen deformations and the proper account of nonuniformities and localization issues are still ongoing research topics, most of the previous experimental work has concentrated on the monotonic shearing behavior of soils (Desrues 1984;Colliat-Dangus, Desrues, and Foray 1988). The research reported here aimed to expand the current state of the knowledge by exploring the development of nonuniformities in sand specimens subjected to up to 4,000 drained compressive load cycles in the triaxial apparatus, as part of experimental and constitutive modeling research at the University of Bristol, United Kingdom (Corti et al 2016). The nonuniformity of deformations across the specimen has been examined by comparing volume changes using both global and local measurements.…”
Section: Introductionmentioning
confidence: 99%
“…While the achievement of precise and accurate measurement of specimen deformations and the proper account of nonuniformities and localization issues are still ongoing research topics, most of the previous experimental work has concentrated on the monotonic shearing behavior of soils (Desrues 1984;Colliat-Dangus, Desrues, and Foray 1988). The research reported here aimed to expand the current state of the knowledge by exploring the development of nonuniformities in sand specimens subjected to up to 4,000 drained compressive load cycles in the triaxial apparatus, as part of experimental and constitutive modeling research at the University of Bristol, United Kingdom (Corti et al 2016). The nonuniformity of deformations across the specimen has been examined by comparing volume changes using both global and local measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant test settings considered are all summarised in Dafalias & Manzari (2004), and enhanced according to the notion of memory surface (Corti et al, 2016). The memory locus is introduced to track fabric effects, and hence simulate realistic sand behaviour under high-cyclic loading.…”
Section: Reference High-cyclic Oedometer Testsmentioning
confidence: 99%
“…Published online at www.geotechniqueletters.com * Faculty of Civil Engineering and Geosciences, Delft University of Technology, Stevinweg 1, 2628 CN Delft (The Netherlands) particularly of the new memory-enhanced bounding surface formulation for sand by Liu et al (Liu et al, 2018a,b). The model belongs in the well-known family of criticalstate SANISAND models (Dafalias & Manzari, 2004), and relies on the use of an additional locus ('memory surface') to capture fabric-related ratcheting/shakedown phenomena (Corti et al, 2016). An opportunity for building further trust about the model has been very recently offered by Park & Santamarina (2018), who published novel data concerning dry sand compaction in high-cyclic oedometer tests (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The reference SANISAND04 model, which is build upon a critical state and bounding surface plasticity framework, includes a fabric-dilatancy tensor to reproduce soil fabric effects. The suitability of combining bounding surface theory and memory surface concept has been proven by the work of Corti et al (2016). Soil fabric and its evolution are recorded by a newly introduced memory surface, enclosing a stress region which the soil feels to have already experienced and thus characterised by high stiffness.…”
Section: Introductionmentioning
confidence: 99%